The Impact of Human Resource Development on Employee Performance at the Education and Culture Office of Wajo Regency - Sumarno, Sumarno; Usman, Muktamir; Fitri, Nurul (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This study aims to examine the impact of human resource development on employee performance at the Education and Culture Office of Wajo Regency. Human resource development refers to the initiatives taken by the organization to enhance employees' skills, knowledge, and capabilities to perform their functions effectively. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 58 respondents chosen from a population of 139 employees at the Education and Culture Office of Wajo Regency. The results of the analysis show that human resource development has a positive effect on employee performance, contributing 10.6%. Overall, employee performance was rated as very good, while human resource development was rated as good. This study is expected to contribute to designing more effective HRD programs and enhancing employee performance at the Education and Culture Office of Wajo Regency.